TEST 4 Dark and Light Triad Traits, Age, and Female Teacher Well-Being – A Parallel Mediation Analysis - Orosova, Olga; Liptakova, Janka; Gajdosova, Beata (European Journal of Mental Health, 2026)
Introduction: Despite its importance, teacher well-being remains underexplored, particularly regarding teacher-related traits. Identifying factors that shape well-being across career stages, especially the relationship between well-being and age, is essential. Aim: The aim of the present study is to examine the association between age, a set of Dark and Light Triad traits, and female teacher well-being indicators. Methods: 1,114 female teachers (mean age = 46, SD = 9.12) completed an online, self-reported questionnaire which included the Short Dark Triad Scale, the Light Triad Scale, and the Teacher Subjective Well-being Questionnaire. Confirmatory factor analysis, Pearson’s correlation, hierarchical regression, moderation, and mediation analyses were carried out. Results: The mediation analysis showed a significant direct effect of older age on higher school connectedness (β = .11, p < .001, 95% CI [.05, .16]) and on higher teaching efficacy (β = .18, p < .001, 95% CI [.13, .23]). Age was positively associated with narcissism, which in turn enhanced both teaching efficacy and school connectedness, as well as with Faith in Humanity, which contributed to higher school connectedness. Conversely, lower levels of Humanism were associated with reduced teaching efficacy. Conclusions: The current study highlights key findings on the relationships between age, Dark Triad and Light Triad traits, and teacher well-being, showing that Narcissism (Dark Triad) and Faith in Humanity or Humanism (Light Triad) significantly mediated the associations between age and school connectedness and teaching efficacy, thereby offering insights into areas necessary to improve well-being throughout female teachers’ careers.